Feasible superadiabatic-based shortcuts for the fast generation of 3D entanglement between two atoms. (12th April 2017) - Yang, Xiao-Qin; Huang, Dian-Yang; Xue, Peng; Gong, Yong-Yong; Wu, Jin-Lei; Ji, Xin
Abstract: We propose a scheme to realize the fast generation of three-dimensional entanglement between two atoms via superadiabatic-based shortcuts in an atom–cavity–fiber system. The scheme is feasible because the counterdiabatic Hamiltonian has the same form as the effective Hamiltonian. Numerical simulations are provided to prove that the scheme is robust against variations in various parameters and against decoherence.